2006
DOI: 10.1002/mma.744
|View full text |Cite
|
Sign up to set email alerts
|

On the heat flux vector for flowing granular materials—Part I: effective thermal conductivity and background

Abstract: SUMMARYHeat transfer plays a major role in the processing of many particulate materials. The heat ux vector is commonly modelled by the Fourier's law of heat conduction and for complex materials such as nonlinear uids, porous media, or granular materials, the coe cient of thermal conductivity is generalized by assuming that it would depend on a host of material and kinematical parameters such as temperature, shear rate, porosity or concentration, etc. In Part I, we will give a brief review of the basic equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…This is simply the well-known constraint anticipated by [18,19], that the thermal conductivity a 1 ≤ 0. In the general case, the thermal conductivity is a second-order tensor.…”
Section: Entropy Analysismentioning
confidence: 96%
See 3 more Smart Citations
“…This is simply the well-known constraint anticipated by [18,19], that the thermal conductivity a 1 ≤ 0. In the general case, the thermal conductivity is a second-order tensor.…”
Section: Entropy Analysismentioning
confidence: 96%
“…For q, we follow Massoudi [18,19]. From mechanics-based arguments, he suggested that the heat flux vector depends not only on the temperature gradient, but also on the motion and the density (or volume fraction) gradient.…”
Section: The Constitutive Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For complex materials, K can also depend on the concentration, the temperature, the shear rate, etc. (see [72,73]). When there is no magnetic field or no nanoparticles present in the fluid, the second order tensor, K, reduces to a scalar and Equation (10) becomes, q = −k∇θ (11) where k is the isotropic thermal conductivity.…”
Section: Heat Flux Vectormentioning
confidence: 98%